Politics as organized combat: New players and new rules of the game in Sweden - Stefan Svallfors (Max Planck Institute for the Study of Societies, 2015)
As Hacker and Pierson (2010) have observed, politics is primarily organization: "organized combat." To understand the outcomes of politics, we have to look at how it is organized over time: by whom and with what resources? I take Sweden as an example of how politics as organized combat has changed quite dramatically in recent decades. Sweden is often cited as an opposite to the United States among the rich capitalist countries, but it has experienced many encompassing policy changes which have not received the attention they deserve. The paper specifies how Swedish organized politics has changed fundamentally, including the dismantling of corporatist arrangements, changes in the economic policy decision-making framework, increased income inequality, weakened political parties and changes in their social bases, the decline of blue-collar union strength, the growth of the policy professionals category, the increased impact of multilevel politics, and the mediatization of politics. Today's amorphous, invisible mode of elite-driven policy-making diverges greatly from the old corporatist structures and is accompanied by dramatically increasing inequality. Even in Sweden, the impact of money on politics has become stronger. The paper discusses what this implies for current politics and policy-making in Sweden. – – Hacker und Pierson (2010) definieren Politik in erster Linie als Kampf zwischen organisierten Interessen, als "organized combat". Um Politikergebnisse zu verstehen, muss die organisatorische Struktur von Politik im Zeitverlauf betrachtet werden: Welche Akteure sind daran beteiligt und welche Ressourcen werden dafür eingesetzt? Am Beispiel von Schweden zeigt das Papier auf, wie drastisch sich Politik im Sinne des organized combat im Laufe der letzten Jahrzehnte verändert hat. Schweden wird unter den modernen Industriegesellschaften oft als Gegensatz zu den Vereinigten Staaten gesehen, hat aber viele einschneidende Politikwechsel erfahren, die bisher nicht ausreichend erforscht worden sind. Die Studie erläutert, wie grundsätzlich sich die organisierte Politik in Schweden verändert hat: Abbau korporatistischer Regelungen, veränderte Rahmenbedingungen für wirtschaftspolitische Entscheidungen, höhere Einkommensungleichheit, geschwächte politische Parteien und ihre veränderte Verankerung in der Gesellschaft, Rückgang gewerkschaftlichen Einflusses, Zuwachs an professionellen Lobbyorganisationen, größerer Einfluss der Mehrebenenpolitik und eine zunehmende Medialisierung. Die amorphe, undurchschaubare und elitengesteuerte Politik von heute unterscheidet sich in hohem Maße von den alten korporatistischen Strukturen und geht einher mit einer dramatisch zunehmenden Ungleichheit. Selbst in Schweden hat der monetäre Einfluss auf Politik zugenommen. Das Papier diskutiert die Auswirkungen dieser Entwicklungen sowohl auf die Tagespolitik als auch auf die politische Entscheidungsfindung in Schweden.
Keywords: 300